2019
DOI: 10.17533/udea.iee.v37n2e06
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of internet use by iranian nursing students. Facilitators and barriers

Abstract: Objective. To evaluate the pattern of internet use and factors that facilitate or dissuade its use among nursing students from a university in Urmia, Iran.Methods. A cross-sectional, descriptive study was conducted with 162 nursing students selected through simple random sampling.Results. The findings indicated that 49.1% of the students used the internet from 15 to 60 min per day. The principal use of the internet was to search for scientific content in the Web. Factors that facilitated internet use were “eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…It is because students usually do not have enough skills to appraise the information on the internet appropriately (Chiu, Liang, & Tsai, 2016). This deficient level can also be caused by English language skills, where those who are proficient in English are better at searching for information using the internet (Shirazi, Heidari, Fard, & Ghodsbin, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It is because students usually do not have enough skills to appraise the information on the internet appropriately (Chiu, Liang, & Tsai, 2016). This deficient level can also be caused by English language skills, where those who are proficient in English are better at searching for information using the internet (Shirazi, Heidari, Fard, & Ghodsbin, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A study on the internet using Iranian nursing students was found that 49.1% of the students used the internet from 15 to 60 minutes per day and nursing students were reported there was 44.8% had accessed computers and 47.6% accessed the internet (18). Framework for the Rational Analysis of Mobile Education (FRAME) model was used in clinical nursing practicum, findings of this study showed students in clinical practicums need learning materials that could be accessed ubiquitously for situated learning inwards, also revealed areas for improvements, covering the hardware scope of the devices, training on the use of apps and institutional support for the maintenance of the devices (19).…”
Section: Using Internet Of Things (Iot)mentioning
confidence: 99%
“…A study on the internet using Iranian nursing students was found that 49% of the respondents used the internet from 15 to 60 minutes per day and nursing students were reported there was 44.8% had accessed computers and 47.6% accessed the internet (18). FRAME model was used in clinical nursing practicum, findings of this study showed students in clinical practicums need learning materials that could be accessed ubiquitously for situated learning inwards, also revealed areas for improvements, covering the hardware scope of the devices, training on the use of apps and institutional support for the maintenance of the devices (19).…”
Section: Using Internet Of Things (Iot)mentioning
confidence: 99%